Cooperative initiatives in brazilian community-based tourism and their effects on sustainable local development - Chagas de Almeida, Thiago; Luiz Emmendoerfer, Magnus (Cooperativismo & Desarrollo, 2025)
Community-Based Tourism (CBT) is an approach to managing self-led visitation activities by community actors through cooperative relationships that prioritize the territory's endogenous resources. Thus, CBT has been carried out by cooperative enterprises that can help to promote Sustainable Local Development (SLD). Despite this, the literature needs to better understand this articulation, especially in the Brazilian context, which does not have consolidated instruments for identifying these enterprises. This paper aims to map Brazilian CBT cooperative initiatives and evaluate their potential impact on SLD. Data collection included a bibliographic review and a survey, with data interpreted using descriptive statistics and thematic content analysis. The findings revealed that many CBT cooperative initiatives have been studied and identified in Brazil, with 103 cases mapped across all regions of the country. Additionally, CBT was found to contribute to SLD through collaborative and co-creative processes that lead to sustainable, endogenous practices across environmental, cultural, economic, political, and social dimensions. This study contributes to identifying CBT cooperative enterprises at the national level and advancing the understanding of their implications for SLD, a subject that warrants further exploration in the literature.
Keywords: Cooperativism; Community-based Tourism; Sustainable Local Development; Collaboration; Co-creation